Drift waves, intense parallel electric fields, and turbulence associated with asymmetric magnetic reconnection at the magnetopause - R. E. Ergun; L.‐J. Chen; V. Wilder; N. Ahmadi; S. Eriksson; M. E. Usanova; K. A. Goodrich; J. C. Holmes; A. P. Sturner; D. M. Malaspina; D. L. Newman; R. B. Torbert; et al. (Geophysical Research Letters)
Abstract Observations of magnetic reconnection at Earth's magnetopause often display asymmetric structures that are accompanied by strong magnetic field (B) fluctuations and large‐amplitude parallel electric fields (E||). The B turbulence is most intense at frequencies above the ion cyclotron frequency and below the lower hybrid frequency. The B fluctuations are consistent with a thin, oscillating current sheet that is corrugated along the electron flow direction (along the X line), which is a type of electromagnetic drift wave. Near the X line, electron flow is primarily due to a Hall electric field, which diverts ion flow in asymmetric reconnection and accompanies the instability. Importantly, the drift waves appear to drive strong parallel currents which, in turn, generate large‐amplitude (~100 mV/m) E|| in the form of nonlinear waves and structures. These observations suggest that turbulence may be common in asymmetric reconnection, penetrate into the electron diffusion region, and possibly influence the magnetic reconnection process.